MEREDUKSI BEBAN ANGIN DENGAN TRANSFORMASI BENTUK TEKNIK EXTRUDE DALAM FOLDING ARCHITECTURE (STUDI KASUS HOTEL MAHKOTA SINGKAWANG) - Gian Vicky Aristo Sinaga; Zairin Zain; Yudi Purnomo (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2023)
Wind load is one of the main calculations in architectural design, and in the initial process, a designer is more dominant in directing shapes based on structure rather than expressing himself in the form of his design work. While form is the basic element that appears in architectural work, there are various methods of finding forms that have appeared in the development of architectural science. For this reason, the concept of folding architecture is focused on how to process shapes, using the